The co‐chaperone p23 promotes prostate cancer motility and metastasis. Issue 1 (6th September 2014) - Querol Cano, Laia; Lavery, Derek N.; Sin, Soraya; Spanjaard, Emma; Brooke, Greg N.; Tilman, Jessica D.; Abroaf, Ahmed; Gaughan, Luke; Robson, Craig N.; Heer, Rakesh; Mauri, Francesco; de Rooij, Johan; et al.
Abstract : Prostate cancer is an androgen receptor (AR)‐dependent malignancy at initiation and progression, therefore hormone therapy is the primary line of systemic treatment. Despite initial disease regression, tumours inevitably recur and progress to an advanced castration‐resistant state a major feature of which is metastasis to the bone. Up‐regulation of AR cofactors and chaperones that overcome low hormone conditions to maintain basal AR activity has been postulated as a mechanism of therapy relapse. p23, an essential component of the apo‐AR complex, acts also after ligand binding to increase AR transcriptional activity and target gene expression, partly by increasing chromatin‐loaded holo‐receptor‐complexes. Immunohistochemical studies have demonstrated increased p23 expression in advanced prostate cancer. Here, we further characterise p23 roles in AR signalling and show that it modulates cytosolic AR levels in the absence of hormone, confirming a chaperoning function in the aporeceptor complex and suggesting p23 upregulates AR signalling at multiple stages. Moreover, p23 protein levels significantly increased upon treatment with not only androgen but also clinically relevant anti‐androgens. This was in contrast to the HSP90 inhibitor 17‐AAG, which did not modulate expression of the cochaperone – important given the HSP90‐independent roles we and others have previously described for p23. Further, we demonstrate p23 is implicated in prostate cancer cell motility and in acquisition of invasiveness capacity through the expression of specific genes known to participate in cancer progression. This may drive metastatic processes in vivo since analysis of prostate tumour biopsies revealed that high nuclear p23 significantly correlated with shorter survival times and with development of metastases in patients with lower grade tumours. We propose that increased p23 expression may allow cells to acquire a more aggressive phenotype, contributing to disease progression, and that p23 is a plausible secondary target in combination with HSP90 inhibition as a potential therapy for advanced prostate cancer. Highlights: We report a novel function for p23 in prostate cancer progression. p23 protein levels increase upon treatment with androgens and anti‐androgens. p23 promotes prostate cancer cell motility and acquisition of invasiveness. High nuclear p23 significantly correlates with shorter survival times in patients. p23 may reprogram gene expression profile into a more metastatic pattern.